Design and synthesis of symmetrical pentamethine cyanine dyes as NIR photosensitizers for PDT. (January 2019) - Ciubini, Betty; Visentin, Sonja; Serpe, Loredana; Canaparo, Roberto; Fin, Andrea; Barbero, Nadia
Abstract: Herein, we report the synthesis and spectroscopic characterization of novel Near Infra-Red (NIR) pentamethine cyanine dyes, as potential photosensitizers for Photodynamic Therapy (PDT) characterized by a strong absorption in the tissue transparency window (600–800  nm). The heteroaromatic benzoindolenine ring of various symmetrical cyanine dyes has been differently functionalized and quaternarized as a result of a structure-activity study and to determine the substituent effect on the cellular uptake, ROS production and photodynamic activity. These probes present low cytotoxicity in dark, but promote phototoxic effect, upon irradiation, in human fibrosarcoma cell line (HT-1080) with interesting and unexpected structure to property activity. Highlights: A new series of symmetrical penthametine cyanine dyes have been synthesized. The dyes have been proposed as photosensitizers (PSs) for Photodynamic Therapy (PDT). The PSs show strong absorption in the tissue transparency window (600–800 nm). The PSs have low cytotoxicity in dark, but promote phototoxic effect, upon irradiation, in human fibrosarcoma cell line.